PERAN MANAJEMEN SUMBER DAYA MANUSIA DALAM MENINGKATKAN KUALITAS TENAGA PENDIDIK DI SMA ISLAMIYAH BAWEAN - Riyawati; Huda, Nurul (Prodi MPI Fakultas Tarbiyah IAIN Madura, 2025)
Human resource management plays a strategic role in improving the quality of teaching staff. This research aims to analyze the implementation of human resource management, identify inhibiting factors, and describe efforts to improve the quality of teaching staff at SMA Islamiyah Bawean. The study employs a qualitative approach with observation techniques, in-depth interviews, and documentation. Research subjects include the principal, vice principal, and teachers selected through purposive sampling. Data analysis uses the Miles and Huberman model with source triangulation validity. The results show that SMA Islamiyah Bawean implements systematic human resource management through structured planning based on semester and annual programs, recruitment based on linearity, development through training and learning communities, performance supervision, as well as financial and non-financial compensation. Obstacles include geographical factors, dual roles of female teaching staff, and lack of understanding of educational psychology, which are addressed through internal training and cooperation with external institutions. The research provides practical references for school administrators and policy input for island education.